Fintech Literature and Inclusion's Impact on MSMEs' in Bandar Lampung - Jaka Darmawan; Ari Purnomo; Bandarsyah Bandarsyah (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The purpose of this research is to determine the impact of financial literacy and fintech on financial inclusion. Purposive sampling was utilized in the sampling procedure, and 97 responses were gathered. According to the findings of this study, Financial Literacy has a considerable impact on Financial Inclusion in MSME Actors. Financial technology has had no substantial impact on MSMEs' financial inclusion in Bandar Lampung City. This research can be used by the Financial Services Authority (OJK) and Bank Indonesia, in collaboration with companies that provide financial products and services, to conduct socialization activities to improve financial literacy among the general public, particularly MSME owners, and to complete consumer protection regulations for financial technology services.Keywords— Financial Literature, Fintech, Inclusion, MSME